PERBANDINGAN PENERAPAN SAK-ETAP DAN PSAK 50 DAN 55 ATAS PENURUNAN NILAI (IMPAIRMENT) PIUTANG PADA PT. BPR MILLENIA - Mandang, Daniela Ribka Frida; Poputra, Agus; Kalalo, Meily (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
One of the bank’s biggest revenue is comes from credit. However in distributing credit to society, there is usually an obstacles of the payment of credit to the bank. The bigger the load of bank to make a reserve fund, bank loss itself will reduce the capital. The goal of this research is to understand the differences of the application of SAK and PSAK 50 and 55 on the declining of the receivable. The object of this thesis research is Bank Perkreditan Rakyat Millenia. The method that is used in this research is descriptive method. The result of this research shows that the company used the impairment of receivable align with SAK ETAP and there are differences between SAK ETAP and PSAK 50 and 55 on impairment of receivable.